Rediscovering old mining activities in the Tatra Mountains - Pawlikowski, Maciej; Wróbel, Marta (Geotourism/Geoturystyka, 2013)
As part of a student project in cooperation with the Tatra National Park we examined the current state of iron ore, manganese ore and polymetallic ore in a few drifts in the Chochołowska and Kościeliska Valleys. Information about the old mining operations in the Western Tatras do not exist in the minds of tourists.An interesting way to show this history could be preparing and sharing parts of the drifts as geoturistic objects. An alternative solution would be to create a trail of old mining and metallurgy in the Tatras, which could help to increase the knowledge about the geology and mining subject among tourists. A combination ofa great mining Tatra history with the attractively designed resultsof geological survey could be a particularly interesting project.